Mediating role of customer satisfaction on service quality and customer loyalty in grocery store in shopping malls in Saudi Arabia - Al Otaibi, Naif Mutlaq (2014)
With a robust economic growth and a young population, Saudi Arabia is presently witnessing a high consumer‟s demand in the food and grocery sector. This has led to a transformation of its retailing industries from the aspect of small and unorganised markets to palatial grocery stalls in the shopping malls. As the number of choices for these markets increases with the entry of new players, retailers need to understand the customers‟ perceptions of the quality of services and products offered. This is crucial towards the survival and competitiveness in the market. The determinants of service quality vary in different industries, countries and individuals. The demographics and lifestyles of customers have been identified as the determinants of service quality. However, the studies done on these two factors are limited in Saudi Arabia. Thus this research attempts to examine the effect of perceived service quality on customer loyalty through mediation of customer satisfaction in the Saudi Arabia grocery store industry. Quantitative research method was employed. This research was conducted at selected major shopping malls in three cities in Saudi namely Riyadh, Jeddah, and Dammam. This is because the total number of people living in these three cities represented 60% of the total population of Saudi. Eight hundred questionnaires were distributed but only 408 questionnaires were found to be useable, yielding a response rate of 51%. The findings revealed that there is a direct relation between perceived service quality and customer loyalty. The findings also showed that a relationship has existed between perceived service quality and customer satisfaction and that the customer satisfaction partly mediated the relationship between the perceived service quality and the store loyalty. The study concludes with some recommendations that can be used to guide the retailers in Saudi Arabia in managing their stores‟ service quality and loyalty.